A systematic review of the epidemiology of cystic fibrosis in arab countries: An update - Samer Hammoudeh; Sarah Aqel; Farha Mukthar; Prem Chandra; Ibrahim A. Janahi (Elsevier, 2024)
Background: This study presents an updated report on the epidemiology of cystic fibrosis (CF) in the Arab region. Objectives: It provides a comprehensive review of existing publications on CF, focusing on the prevalence and/or incidence in the period span from year 2019-2023. Methods: A search was conducted primarily through PubMed, followed by the snowballing technique to identify additional studies. Results: A total of 10 articles were identified. Conclusion: This study highlights the pressing need for extensive research, multi-country collaborations, and the establishment of CF registries to enhance our understanding and management of CF in the Arab world.